Synergistic Nico2s4/Graphene Quantum Dot Nanosheets for Superior Electrochemical Performance in Asymmetric Supercapacitors - Radhalayam, D (ELSEVIER, 2025)
Nanostructured materials with diversified morphologies have proven their uniqueness in electrochemical energy storage by enhancing the charge storage performance. In particular, transition metal sulfides, known for their rich redox reactions, are extensively explored as promising electrode materials for next-generation super-capacitors. However, severe aggregation often restricts ion-accessible electroactive sites, leading to a decline in capacitance. To address this challenge, the present study synthesizes NiCo2S4(NCS)@GQDs-x composite nano-sheet (NS) structures by integrating GQDs with NCS via hydrothermal method. The hierarchical nanosheet structures of NCS@GQDs-x provide abundant active sites and promote fast electron transfer due to the synergistic effect between GQDs and NCS. Among the synthesized nanocomposites, NCS@GQDs-7 exhibited superior capacitive performance (1577 F g-1 @ 0.5 A g-1) owing to its uniformly distributed nanosheet-like morphology, excellent conductivity, and efficient electron and ion-transport pathways. Furthermore, the assembled asymmetric supercapacitor (ASC) device achieves an excellent energy density of 29.25 Wh/kg at a power density of 402 W/kg, with outstanding capacitance retention of 91.5 % even after 10000 charge-discharge cycles. The remarkable electrochemical properties of the NCS@GQDs-7 electrode may testify to one of the potential candidates in capacitive science for the development of next-generation high-performance supercapacitors.